Optimization of Vehicle Routing Problem Using Particle Swarm Optimization: A Case Study Watering Plants in Yogyakarta City - Riski Andriyansah; Utaminingsih Linarti (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
Dinas Lingkungan Hidup (DLH) Yogyakarta City always tries to monitor, control, and control activities regarding all aspects of the environment, one of which is watering plants. The right path must be selected so as not to exceed the time limit set. This study aims to determine the direction of watering plants in Sector 3 for Vehicle Route Problem (VRP) using the Particle Swarm Optimization (PSO) and compare the performance results of the PSO method with the Genetic Algorithm (GA) in previous studies. The VRP criteria are heterogeneous fleet, intermediated facility, multi-trip, split delivery, and times window (VRPHFIFMTSDTW). The results of the comparison between the two methods, namely, the GA method, are better than the PSO method in terms of computational time efficiency and fitness value. The total travel time for the GA method is 22 minutes, or 2.1% faster than the PSO method. In contrast, the total distance traveled by the PSO method is 345 meters shorter than the GA method. These two methods' results are also excellent compared to the current watering route. The difference in total mileage is about 20.4%, and total travel time is about 11.7% between the two methods.